Advances in polymer science = Fortschritte der Hochpolymeren-Forschung. Volume 8 - Cantow, H. J. (Springer-Verlag, 1971)
Kinetic theory and rheology of Dumbbell suspension with Brownian motion / H. R. Warner jr, D, C. Evans ; The measurement of molecular orientation in polymeric solids / G. L. Wilkes ; The propagation rate-constants in cationic polymerisations / P. H. Plesch ; Reinforcement of elastomers by carbon black / G. Kraus
Keywords: polymery; polymerizace; instrumentální analýza; reologie; saze; elastomery; plniva; polymers; polymerization; instrumental analysis; rheology; carbon-black; elastomers; fillers (materials); sborníky; miscellanea